Women’s labor and everyday life in the great patriotic war years - Zhuldyz Karsybayeva, Kair Tleugabylova, Zauresh Saktaganova,Kymbat Abdrakhmanov, Svetlana Yeleukhanova, Bibigul Dosova, (Opción, 2020)
Based on archival materials and a comparative historical method, this article analyzes the labor contribution of women to the formation of the military mobilization economy based on the materials of the Kazakh SSR. As a result, poor conditions at work and in everyday life often served as a reason for the violation of labor discipline and staff turnover, therefore, documents often contain facts of “labor desertion”, harsh measures were taken, but wartime punishment was reduced under this article. In conclusion, extremely difficult living and working conditions could cause widespread discontent in certain communities.